Effect of lifestyle interventions on glucose regulation among adults without impaired glucose tolerance or diabetes: A systematic review and meta-analysis. (January 2017) - Zhang, Xuanping; Imperatore, Giuseppina; Thomas, William; Cheng, Yiling J.; Lobelo, Felipe; Norris, Keri; Devlin, Heather M.; Ali, Mohammed K.; Gruss, Stephanie; Bardenheier, Barbara; Cho, Pyone; Garcia de Quevedo, Isabel; et al.
Highlights: Lifestyle interventions significantly improved FPG, HbA1c, FI, HOMA-IR, and bodyweight among adults without IGT or diabetes. D and PA + D interventions had larger effects on glucose reduction than PA alone. Lifestyle interventions were effective across a wide variation of follow-up durations. Abstract: This study systematically assessed the effectiveness of lifestyle interventions on glycemic indicators among adults (⩾18 years) without IGT or diabetes. Randomized controlled trials using physical activity (PA), diet (D), or their combined strategies (PA + D) with follow-up ⩾12 months were systematically searched from multiple electronic-databases between inception and May 4, 2016. Outcome measures included fasting plasma glucose (FPG), glycated hemoglobin (HbA1c), fasting insulin (FI), homeostasis model assessment-estimated insulin resistance (HOMA-IR), and bodyweight. Included studies were divided into low-range (FPG <5.5 mmol/L or HbA1c <5.5%) and high-range (FPG ⩾5.5 mmol/L or HbA1c ⩾5.5%) groups according to baseline glycemic levels. Seventy-nine studies met inclusion criteria. Random-effect models demonstrated that compared with usual care, lifestyle interventions achieved significant reductions in FPG (−0.14 mmol/L [95%CI, −0.19, −0.10]), HbA1c (−0.06% [−0.09, −0.03]), FI (%change: −15.18% [−20.01, −10.35]), HOMA-IR (%change: −22.82% [−29.14, −16.51]), and bodyweight (%change: −3.99% [−4.69, −3.29]). The same effect sizes in FPG reduction (0.07) appeared among both low-range and high-range groups. Similar effects were observed among all groups regardless of lengths of follow-up. D and PA + D interventions had larger effects on glucose reduction than PA alone. Lifestyle interventions significantly improved FPG, HbA1c, FI, HOMA-IR, and bodyweight among adults without IGT or diabetes, and might reduce progression of hyperglycemia to type 2 diabetes mellitus.